Comparatively Studying Educational System (Re)Building Cross-Nationally: Another Agenda for Cross-National Educational Research?. Issue 6 (September 2019) - Spillane, James P.; Peurach, Donald J.; Cohen, David K.
Institutional theory, an important research tradition in analysis of schooling, has examined the development of mass schooling in the United States and worldwide. But research in this tradition has given little attention to the internal working of mass school systems, to problems of inequality and the quality of instruction, or to relating those problems to the organization and management of mass school systems. Building on the first three articles, which document how education system building has become a key instrument in efforts to improve the quality and equality of educational opportunity for students, we argue for a program of comparative research on education system building cross-nationally. We outline a program of research that would extend our comparative approach to studying school systems' efforts to build, use and manage educational infrastructure as they attempt to transition to education systems in the United States by including such efforts in several other nations.